Meta analysis of resting frontal alpha asymmetry as a biomarker of depression - Yiwen Luo; Mingcong Tang; Xiwang Fan (npj Mental Health Research)
Abstract This meta-analysis investigated resting frontal alpha asymmetry (FAA) as a potential biomarker for major depressive disorder (MDD). Studies included articles utilizing FAA measure involving EEG electrodes (F3/F4, F7/F8, or Fp1/Fp2) and covering both MDD and controls. Hedges’ d was calculated from FAA means and standard deviations (SDs). A systematic search of PubMed through July 2023 identified 23 studies involving 1928 MDD participants and 2604 controls. The analysis revealed a small but significant grand mean effect size (ES) for FAA (F4 − F3), suggesting limited diagnostic value of FAA in MDD. Despite the presence of high heterogeneity across studies, subgroup analyses did not identify significant differences based on calculation formula, reference montage, age, or depression severity. The findings indicate that FAA may have limited standalone diagnostic utility but could complement existing clinical assessments for MDD, highlighting the need for a multifaceted approach to depression diagnosis and prognosis.